Does social policy crowd out or crowd in social trust? The perspectives of transfer share, low-income targeting, and universalism - Naoki Akaeda (Luxembourg Income Study (LIS), 2023)
In recent decades, a great deal of international comparative research has examined whether social policy crowds out or crowds in social trust. Although previous studies have made significant advances, we still have much to learn. First, the proxies of social policy adopted by earlier publications may confound the levels and distribution of welfare provisions. Second, little research has explored whether two important distribution patterns of welfare provisions-lowincome targeting and universalism-crowd out or crowd in social trust in international comparative analysis. Against this backdrop, this study focuses on the distinctive roles of three dimensions of welfare transfers, such as transfer share, low-income targeting, and universalism, in social trust. For the analysis, the present study utilizes data from the Luxembourg Income Study (LIS) Database, merged data from the World Values Survey (WVS) and the European Values Study (EVS), and the two-way fixed-effects model. Through an international comparative analysis, this study clarified that low-income targeting crowds out social trust, while universalism crowds in social trust. These results suggest that (1) low-income targeting may have a side effect on social trust and (2) universalism and social trust may partly explain the selfperpetuating process of the welfare state.
Keywords: 330; welfare transfers; social trust; crowd out; crowd in; two-way fixed-effects model